Online Validation of Relay based Identification and Controller Design with an Anti-Reset Windup for a Binary Distillation Column - Sarath Yadav, Eadala; Indiran, Thirunavukkarasu; Priya Selvanathan, Shanmuga; UG, Ganesh (International Journal of Engineering and Technology, 2018)
Sequential auto-tuning based model identification is a closed loop approach, which has an extensive benefit compared to conventional methods because of user defined manipulated gain to the process within the verge of instability. Model parameters estimation of multi input multi output process is challenging because of existence of multivariable interaction among the variables. In this paper ideal relay is used as a sequential basis for binary distillation column in real time. Obtaining sustained oscillations in conventional methods is based on trial and error, benefit of relay is that oscillations can be generated as scaling of user defined gains. Predictive PI control algorithm is implemented. Results depicts the efficiency of methodology and importance of anti-reset term in the algorithm.Â Â